Synthesis, characterization and thermal behaviour of solid state compounds of 2-chlorobenzylidenepyruvate with trivalent aluminium, gallium, indium and scandium metals - Bannach, Gilberto; Schnitzler, Egon; Ionashiro, Massao (Eclética Química, 2003)
Solid state compounds M-2-Cl-BP, where 2-Cl-BP is 2-chlorobenzylidenepyruvate and M represents Al, Ga, In, and Sc were prepared. X-ray powder diffractometry, infrared spectroscopy and simultaneous thermogravimetry-differential thermal analysis (TG-DTA), have been used to characterize and to study the thermal behavior of these compounds. The results provided information concerning the stoichiometry, crystallinity, thermal stability and thermal decomposition of the compounds.